A comparative study of gradient boosting algorithms and transformer neural networks for classification problems in the tabular data domain - Albertyn, Carla (Stellenbosch : Stellenbosch University, 2025)
Albertyn, C. 2025. A comparative study of gradient boosting algorithms and transformer neural networks for classification problems in the tabular data domain. Unpublished masters thesis. Stellenbosch: Stellenbosch Univeristy [online]. Available: https://scholar.sun.ac.za/items/1426022c-fbf0-44eb-ab74-43df924264d6